2014
DOI: 10.1186/1475-2875-13-91
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of biomarkers for parasite burden and immune activation with acute kidney injury in severe falciparum malaria

Abstract: BackgroundAcute kidney injury (AKI) complicating severe Plasmodium falciparum malaria occurs in up to 40% of adult patients. The case fatality rate reaches 75% in the absence of renal replacement therapy (RRT). The precise pathophysiology of AKI in falciparum malaria remains unclear. Histopathology shows acute tubular necrosis with localization of host monocytes and parasitized red blood cells in the microvasculature. This study explored the relationship of plasma soluble urokinase-type plasminogen activator r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 37 publications
1
47
1
Order By: Relevance
“…However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients. In comparison, the plasma level of suPAR was found to have a good predictive value for mortality in patients with mild malaria, with a corresponding low mortality, but lost its predictive value in severe malaria, with a corresponding high mortality [22]. Notably, the predictive value of suPAR did not improve with less severe forms of ARDS (i.e., mild or moderate ARDS).…”
Section: Discussionmentioning
confidence: 87%
“…However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients. In comparison, the plasma level of suPAR was found to have a good predictive value for mortality in patients with mild malaria, with a corresponding low mortality, but lost its predictive value in severe malaria, with a corresponding high mortality [22]. Notably, the predictive value of suPAR did not improve with less severe forms of ARDS (i.e., mild or moderate ARDS).…”
Section: Discussionmentioning
confidence: 87%
“…42 Indirect measures of parasite sequestration and monocyte activation levels have been found to correlate with renal failure requiring replacement therapy. 43 Mild to moderate glomerulonephritis has also been observed as seen by glomerular hypercellularity and collapse. 40 Histological assessment of renal tissue from severe malaria patients for ZO-1 distribution reveals marked and diffuse reductions in glomerular ZO-1 staining including within glomerular endothelial cells suggestive of extensive paracellular junction disruption.…”
Section: Clinical Evidence Of Barrier Dysfunction In Severe Malariamentioning
confidence: 98%
“…143 The resulting optically transparent tissue allows high resolution 3D imaging of large (cm) sections of tissue and could provide a more comprehensive overview of endothelial junctional protein distribution in severe malaria. Beyond the brain and lung, applying these methods to the analysis of renal tissue from patients with severe malaria could provide additional insight into acute kidney injury in both children 144 and adults 43 which is associated with renal endothelial cell hypertrophy and cytoplasmic vacuolation as well as monocyte infiltration. 42 …”
Section: Imaging Studiesmentioning
confidence: 99%
“…To best of our knowledge there is no research has measured this parameter regarding the use of GIT-27 against renal ischemia reperfusion injury. However, [23] up regulation of NGAL in renal tubule cells may be induced by local release of cytokines from monocytes in the microcirculation after ischemic injury [24] Nils and others [25] demonstrated that in vascular smooth muscle cells NGAL expression is induced in response to vascular injury and depends on nuclear factor kappa B (NF-kB) expression [26], and upon activation of Toll-like receptors (TLRs) on immune cells establishing an acute phase response [27]. In I/R group, generally all intersections of the most of rat sections of this group indicated tubular cell swelling, brush border loss, nuclear condensation, with more than 66% of the tubular profile demonstrating nuclear loss.…”
Section: Discussionmentioning
confidence: 99%